Using Polar Faculae to Determine the Sun's High-Latitude Rotation Rate. I. Techniques and Initial Measurements ... - Sheeley, Neil R. (arXiv, 2024)
This paper describes a new way of determining the high-latitude solar rotation rate statistically from simultaneous observations of many polar faculae. In this experiment, I extracted frames from a movie made previously from flat-fielded images obtained in the 6767 A continuum during February 1997-1998 and used those frames to construct space-time maps from high-latitude slices of the favorably oriented south polar cap. These maps show an array of slanted tracks whose average slope indicates the east-west speed of faculae at that latitude, Ls. When the slopes are measured and plotted as a function of latitude, they show relatively little scatter 0.01-02 km/s from a straight line whose zero-speed extension passes through the Sun's south pole. This means that the speed, v(Ls), and the latitudinal radius, R cos(Ls), approach 0 at the same rate, so that their ratio gives a nearly constant synodic rotation rate 8.6 deg/day surrounding the Sun's south pole. A few measurements of the unfavorably oriented north ... : 13 pages, 8 figures ...